The Role of Parents in Increasing the Responsibility Level of Students Toward Literacy Activities in Grade III at Sahabat Cendikia Islamic Elementary School, Ternate City - Iwan Irawan; Jusmin Hj Wahid; Amirudin Ais; Marwah Tonggol (Universitas Muhammadiyah Enrekang, 2026)
This study aims to describe the role of parents in increasing the level of responsibility among third-grade students toward reading and writing literacy activities at Sahabat Cendikia Islamic Elementary School, Ternate City. The research was motivated by the low interest in reading and writing habits among students, which negatively affects their basic literacy skills. Parents play a strategic role in shaping children’s habits and attitudes of responsibility toward literacy through habituation, mentoring, and motivation at home. This study employed a qualitative descriptive method. Data were collected through semi-structured interviews, questionnaires, and observations involving 25 parents of Grade III students. The findings reveal that most parents actively contribute to building students’ responsibility by allocating specific time for reading, establishing regular writing routines, assigning responsibility for book care, providing consistent motivation, and serving as positive role models in literacy activities. Consistent parental involvement has a significant positive influence on students’ completion of school literacy tasks. The study concludes that the success of literacy learning in primary schools is not determined solely by teachers but also requires active support from parents at home. Therefore, strengthening school-family collaboration is essential to create a conducive literacy-rich environment for students.